A Study of human relations principles and practices in Torres-Bugallon (1958)
As practiced in Torres Bugallon, it is evident that good human relations vitally promote the success of a community school. Its absence may spell failure. The district supervisor, the teachers, and lay leaders interviewed point to to the excellent human relations of Mrs. Bernardino as the most important factor in the success of the people in the community are appraised and shared with honor and success achieved by the school. It is now clear that the equality of human relations substantially affects the quality of the community school.
Keywords: Interpersonal relations; Community and school -- Philippines -- Bulacan; Community schools -- Philippines -- Bulacan